Significance of nanoparticle radius, inter‐particle spacing, inclined magnetic field, and space‐dependent internal heating: The case of chemically reactive water conveying copper nanoparticles. Issue 4 (23rd December 2021) - Sun, Xiaoxiang; Animasaun, Isaac Lare; Swain, Kharabela; Shah, Nehad Ali; Wakif, Abderrahim; Olanrewaju, Philip Oladapo
Abstract: Sequel to the biocompatibility, physicochemical properties, high electrical conduction of copper nanoparticles over an inclined surface, little is known on the significance of nanoparticle radius, and inclined magnetic field on the dynamics of chemical reactive water conveying copper nanoparticles through a porous medium in the presence of Joule heating and spacing heating. In this case, there exists convective heating of the inclined surface due to thermal and significant concentration at the wall. The similarity solution of the problem was obtained using a suitable similarity solution and a numerical solution of the corresponding boundary value problem of the ordinary differential equation was sought for using MATLAB‐based bvp4c package. Based on the analysis, it is worth concluding that inter‐particle spacing not only exists but is also capable to increase the viscosity thus causing a decline in the velocity. The temperature distribution is an increasing function of the inclined magnetic field parameter. The rate of decrease in the local skin friction coefficients due to enhancement in the angle of inclination of the magnetic field is optimal when the radius of nanoparticles is large. Abstract : Sequel to the biocompatibility, physicochemical properties, high electrical conduction of copper nanoparticles over an inclined surface, little is known on the significance of nanoparticle radius, and inclined magnetic field on the dynamics of chemical reactive water conveying copper nanoparticles through a porous medium in the presence of Joule heating and spacing heating. In this case, there exists convective heating of the inclined surface due to thermal and significant concentration at the wall.…